2017
DOI: 10.4196/kjpp.2017.21.6.599
|View full text |Cite
|
Sign up to set email alerts
|

JPH203, a selective L-type amino acid transporter 1 inhibitor, induces mitochondria-dependent apoptosis in Saos2 human osteosarcoma cells

Abstract: Most normal cells express L-type amino acid transporter 2 (LAT2). However, L-type amino acid transporter 1 (LAT1) is highly expressed in many tumor cells and presumed to support their increased growth and proliferation. This study examined the effects of JPH203, a selective LAT1 inhibitor, on cell growth and its mechanism for cell death in Saos2 human osteosarcoma cells. FOB human osteoblastic cells and Saos2 cells expressed LAT1 and LAT2 together with their associating protein 4F2 heavy chain, but the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Of them, several reports have provided the molecular analysis and showed the anti-tumor proliferation mechanism by western blot assay, through downregulating the phosphorylation of mTOR pathway proteins such as p70S6K, and S6, and upregulating the phosphorylation of 4EBP1 3133 . Moreover, JPH203 activated the mitochondria-dependent apoptotic signaling pathway by upregulating pro-apoptotic factors, such as Bad, Bax, and Bak, and the active form of caspase-9, and downregulating anti-apoptotic factors, such as Bcl-2 and Bcl-xL in human osteosarcoma Saos2 cells 35 . The other groups also showed induction of the apoptosis in oral cancer YD-38 cells 36 .…”
Section: Discussionmentioning
confidence: 98%
“…Of them, several reports have provided the molecular analysis and showed the anti-tumor proliferation mechanism by western blot assay, through downregulating the phosphorylation of mTOR pathway proteins such as p70S6K, and S6, and upregulating the phosphorylation of 4EBP1 3133 . Moreover, JPH203 activated the mitochondria-dependent apoptotic signaling pathway by upregulating pro-apoptotic factors, such as Bad, Bax, and Bak, and the active form of caspase-9, and downregulating anti-apoptotic factors, such as Bcl-2 and Bcl-xL in human osteosarcoma Saos2 cells 35 . The other groups also showed induction of the apoptosis in oral cancer YD-38 cells 36 .…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, the selective inhibition of LAT1 by JPH203 has been demonstrated. Several groups reported that JPH203 inhibits the proliferation of cancer cells by inhibiting L-leucine uptake 13,18,26 , LAT1 has been shown to affect cancer cell proliferation through the mTOR signalling pathway in pancreatic cancer 27 , lung cancer 28 , and prostate cancer 6,29 . Leucine is an essential amino acid that must be taken from outside the cells and activates mTOR signals.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth to note that the tyrosine analog JPH203, previously known as KYT-0353, is a potent inhibitor (Oda et al, 2010 ) both in vitro and in mouse model of HT-29 tumors (colon cancer) (Oda et al, 2010 ; Wempe et al, 2012 ; Toyoshima et al, 2013 ). The molecular mechanism of action of JPH203, investigated using osteosarcoma cell line (Choi et al, 2017 ), consists in activating the mitochondrial pro-apoptotic pathway. This inhibitor is effective also in different type of cancers (Rosilio et al, 2015 ; Hayashi et al, 2016 ; Choi et al, 2017 ; Otsuki et al, 2017 ; Yothaisong et al, 2017 ).…”
Section: Lat1 Druggability and Clinical Outcomesmentioning
confidence: 99%
“…The molecular mechanism of action of JPH203, investigated using osteosarcoma cell line (Choi et al, 2017 ), consists in activating the mitochondrial pro-apoptotic pathway. This inhibitor is effective also in different type of cancers (Rosilio et al, 2015 ; Hayashi et al, 2016 ; Choi et al, 2017 ; Otsuki et al, 2017 ; Yothaisong et al, 2017 ). Moreover, a synergistic effect with metformin is observed in a cell line of HNC (Head and Neck Cancer) in vitro and in mouse-transplanted model (Ueno et al, 2016 ).…”
Section: Lat1 Druggability and Clinical Outcomesmentioning
confidence: 99%